Melt‐mixing small diameter glass fiber and epoxy resin in internal mixer without solvent for strain gage substrate. Issue 4 (21st June 2016) - Han, Renlu; Wang, Gaoqiang; Hou, Yafei; Wang, You
Abstract : Glass fiber reinforced epoxy is prepared by melt‐mixing glass fiber of 1 μm in diameter and epoxy resin without adding solvent in internal mixer. Strain gage substrate is made of the prepared glass fiber‐reinforced epoxy using a three‐roller grinder and characterized by SEM, DSC, DMA, and TGA. The results indicate the uniform and dense distribution of glass fibers in epoxy matrix enables the storage modulus, tan delta, heat distortion temperature, creep resistance, and thermal stability of glass fiber‐reinforced epoxy strain gage substrate to be better than those of neat epoxy strain gage substrate. POLYM. COMPOS., 39:1321–1330, 2018. © 2016 Society of Plastics Engineers